Hypoglycaemic and protective effects of Benincasa hispida aqueous extract in streptozotocin-induced diabetic rats - Fatariah Zakaria; Wan Rosli Wan Ishak; Wan Amir Nizam Wan Ahmad; Sabreena Safuan; Tengku Alina Tengku Ismail (Penerbit Universiti Kebangsaan Malaysia, 2022)
Benincasa hispida (BH) contains a range of compounds which play important roles in treating human illnesses. This study was undertaken to evaluate the hypoglycaemic and protective effects of BH fruit on diabetes mellitus (DM) rats. The dose of 250 mg/kg of B. hispida aqueous extract (BHE) is the most effective dose in decreasing blood glucose level (BGL). After eight weeks of treatment, the BGL of BHE-treated DM rats (21.4±1.0 mmol/l) was found to be significantly lower than control DM rats (30.1±3.8 mmol/l). The weight of BHE-treated rats was also higher compared to the other DM groups. Overall, the biochemical evaluation of BHE-treated rats such as lipid profile, liver function test, kidney function test and HbA1c showed an improvement in biomarker values compared to the other groups. There were enhancements in liver and kidney structures of the BHE-treated group compared to those with metformin treatment, which indicated the protective effects of BH on the impaired organ structure. These findings suggest that BHE treatment exerts hypoglycaemic and protective effects in DM by decreasing the BGL, improving weight and biochemical parameters, as well as protecting liver and kidney from serious damage.